The Public on the Public - Westall, C. author. aut Link
VIII, 152 p.
Keywords: In Britain, the resistance to popular determination allowed by the financial construct of the public has been so successful that this term, public, must be re-read as politically paralyzing. The problem, our problem, is the public - which we are so often told will bring us together and provide for us - and it is this we must move beyond.